PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL MENGGUNAKAN APLIKASI FILMORA PADA MATA PELAJARAN GEOGRAFI MATERI FLORA DAN FAUNA DI INDONESIA DAN DUNIA SMA NEGERI 1 DULUPI - annisa, sitti; Lihawa, Fitryane; Mohamad, Nurdin (Social Landscape Journal, 2024)
This research is research into the development of audio-visual based learning media using the Filmora application. This research aims to produce audio-visual based learning media using the Filmora application on flora and fauna material in Indonesia and the world. This research uses a development research method using the ADDIE model as an approach in compiling learning media. In this research there are 5 stages, namely the analysis stage, design stage, development stage, implementation stage and evaluation stage. The results of the development research were obtained from the validator assessment results which showed that this learning media was declared suitable for use and very valid. The assessment given to each statement is as follows: from product design expert validation it is declared very valid with a rating result of 84%, from material/content experts it is declared very valid with a rating result of 91.1% and the learning expert in this case is a geography teacher declared very valid with a rating result of 90.3% and the average student response to learning media was 89.1%, which means it was classified as very good media. The conclusion of this research is that audio-visual based learning media using the Filmora application developed by researchers is declared suitable for use in the learning process.